2006
DOI: 10.1037/0735-7044.120.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Selective lesions of the nucleus basalis magnocellularis impair cognitive flexibility.

Abstract: The authors tested the hypothesis that the cholinergic nucleus basalis magnocellularis (NBM) is involved in solving problems requiring cognitive flexibility. Rats with 192 IgG-saporin lesions of the NBM were assessed for perseveration (i.e., cognitive inflexibility) in the serial reversal of an operant discrimination and during subsequent extinction testing. It was hypothesized that the NBM lesion and control groups would not differ in the acquisition of the initial, simple discrimination, because this task do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Learning deficits in the Morris water maze, a classic hippocampal-dependent task, were also found immediately after adolescent ethanol exposure, and this effect persisted into adulthood [11]. Other studies reported deficits during reversal learning (but not acquisition) in the Morris water maze[14] and Barnes maze [13] – two tasks thought to be hippocampally-dependent, although other brain regions, like the OFC [46] and basal forebrain [47], are thought to contribute to reversal learning per se. The results of this study contribute to the mounting evidence that adolescent ethanol exposure may lead to long-lasting deficits in cognition, particularly affecting tasks that are relatively hippocampal-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Learning deficits in the Morris water maze, a classic hippocampal-dependent task, were also found immediately after adolescent ethanol exposure, and this effect persisted into adulthood [11]. Other studies reported deficits during reversal learning (but not acquisition) in the Morris water maze[14] and Barnes maze [13] – two tasks thought to be hippocampally-dependent, although other brain regions, like the OFC [46] and basal forebrain [47], are thought to contribute to reversal learning per se. The results of this study contribute to the mounting evidence that adolescent ethanol exposure may lead to long-lasting deficits in cognition, particularly affecting tasks that are relatively hippocampal-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion studies of the basal forebrain demonstrate its involvement in behavioral flexibility (Cabrera et al, 2006; Tait and Brown, 2008). Non-selective ibotenic acid lesions in the basal forebrain impair reversal learning but leaves set shifting intact (Tait and Brown, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These capacities are acquired during development as a result of synaptic maturation in the sensory circuit and can be improved by training in adulthood (Sanes and Woolley, 2011). Lesions of cortical cholinergic fibers can result in decreased detection, identification, and localization of stimuli and impaired learning, storage, and flexible retrieval of sensory associations (Berger-Sweeney et al, 2000; Butt et al, 2002; Cabrera et al, 2006; Leach et al, 2013; Vale-Martinez et al, 2002). …”
Section: Improving Perception By Manipulating Neuromodulationmentioning
confidence: 99%